2013
DOI: 10.1177/0954405413502023
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of green properties of iron/jet-milled grey cast iron compacts by response surface method

Abstract: Grey cast iron powder was produced from grey cast iron scraps by jet milling method and mixed with commercial pure iron powder. The morphology of the produced powders and characteristics of the powder mixtures were investigated. The mathematical models were successfully developed to predict green properties of iron/jet-milled grey cast iron compacts using response surface methodology. Using response surface methodology, the effects of the percentage of jetmilled cast iron powder and compaction pressure on gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…However, a different trend is observed in the case of the parameter CIP . By increasing CIP from 30% to 50%, a slight difference is seen in the strength values, while the green density and green strength 9 and the sintered density decrease by increasing CIP . This trend can be explained by interpreting the microstructures of Figure 8.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…However, a different trend is observed in the case of the parameter CIP . By increasing CIP from 30% to 50%, a slight difference is seen in the strength values, while the green density and green strength 9 and the sintered density decrease by increasing CIP . This trend can be explained by interpreting the microstructures of Figure 8.…”
Section: Resultsmentioning
confidence: 93%
“…In our previous work, 9 the green properties of iron/ jet-milled grey cast iron compacts were investigated and optimized by response surface methodology (RSM). The results demonstrated that jet-milled grey cast iron powders have the capability to be used in as-milled state in combination with iron powder for producing green compacts in industrial scales with acceptable green properties.…”
Section: Introductionmentioning
confidence: 99%
“…RSM is a group of statistical and mathematical techniques that are useful for modelling and predicting the output of interest influenced by some input variables with the objective of optimising this output [8][9][10][11]. RSM also describes the relationships among one or more measured outputs and the vital controllable input factors [12].…”
Section: Response Surface Methodology (Rsm)mentioning
confidence: 99%
“…As a result, the majority of the chips available for recycling are sourced from other machining operations such as turning, drilling, end-milling, and shaping. Various shapes of metal chips produced from machining processes [9]: (a) grey cast iron [13]; (b) stainless steel [14]; (c) AA6060 aluminum alloy [15]; (d) AZ31B magnesium alloy [16]; (e) Figure 1. Various shapes of metal chips produced from machining processes [9]: (a) grey cast iron [13];…”
Section: Introductionmentioning
confidence: 99%